APPLICATION OF SEMANTIC WEB TO CREATE A COLLABORATIVE EDUCATIONAL SPACE - Glibovets, M.M. (Journal of Information Technologies in Education (ITE), 2010)
The prospects for the use of Semantic Web technologies in e-learning are considered. Using agent technology to create an interactive learning environment, endowed with powerful collaboration tools and the use of Web-services makes it possible to consider a holistic collaborative educational space. An analysis of the architecture of the space and the prospects for its development are described